Les périples de Kalila et Dimna: Itinéraires de fables dans les arts et la littérature du monde islamique : The Journeys of Kalila and Dimna: Itineraries of Fables in the Arts and Literature of the Islamic World - Khiari, Aïda El; Vernay-Nouri, Annie; Perrière, Eloïse Brac de la (Brill Studies in Middle Eastern Literatures, 2022)
Kalīla wa-Dimna is one of the best-known texts of medieval Arabic literature and counts among the most illustrated works in the Islamic world. The extent of the corpus and its journey through the ages make it the ideal material for a reflection on the evolution of iconography in Islamic art. The studies gathered in this volume edited by Eloïse Brac de la Perrière, Aïda El Khiari and Annie Vernay-Nouri, showcase a wide diversity of approaches that convincingly crosses textual investigation, codicology, iconographical study, and physico-chemical analyses. They explore new tracks, either by devoting themselves to the examination of unknown or rarely studied manuscripts, or by proposing innovative readings of this extremely rich work that is Kalīla wa-Dimna. Kalīla wa-Dimna est l'un des textes les plus célèbres de la littérature arabe médiévale et compte parmi les œuvres les plus illustrées du monde islamique. L'étendue du corpus et son parcours à travers les âges en font un extraordinaire matériau pour mener une réflexion sur l'image dans l'histoire des arts islamiques. Les études rassemblées dans ce volume dirigé par Eloïse Brac de la Perrière, Aïda El Khiari et Annie Vernay-Nouri, mettent en œuvre une grande diversité d'approches croisant investigation textuelle, codicologique, iconographique et analyses physico-chimiques. Elles explorent toutes des pistes nouvelles, soit en se consacrant à l'examen de manuscrits inédits ou très rarement étudiés, soit en proposant des lectures innovantes de cette œuvre extrêmement riche qu'est Kalīla wa-Dimna. Contributors: Eloïse Brac de la Perrière, Nathalie Buisson, Mounia Chekhab-Abudaya, Frantz Chaigne, Anna Contadini, Jean-Charles Coulon, Françoise Cuisance, Aïda El Khiari, Rajana Fatima Amalarajah, Béatrice Gruendler, Mika Natif, Bernard O'Kane, Hoa Perriguey, Yves Porter, Francis Richard, Valérie Saurel, Christine Van Ruymbeke, Annie Vernay-Nouri.